Implementasi Aplikasi Sipades 3.0 Untuk Meningkatkan Transparansi Dan Akuntabilitas Pengelolaan Aset Di Desa Kandangan - Aisyah Zarkasi; Waspodo Tjipto Subroto (Advances In Education Journal, 2026)
This study is motivated by the low transparency and accountability in village asset management due to manual recording and limited information access. It aims to analyze the acceptance of the Village Asset Management System (SIPADES 3.0) in improving transparency and accountability in Kandangan Village. The research uses a qualitative case study approach conducted in Kandangan Village, Cerme District, Gresik Regency, involving the village head, secretary, SIPADES operator, and community members. Data were collected through interviews, observation, and documentation, then analyzed using data reduction, data display, and conclusion drawing with triangulation. The results show that SIPADES 3.0 improves asset recording order, facilitates inventory management, and enhances reporting quality. Transparency and accountability have increased, although challenges remain in limited human resources and digital literacy. Overall, SIPADES 3.0 is effective in supporting transparent and accountable village asset management, but strengthening officials’ capacity and infrastructure remains necessary.